2007
DOI: 10.1111/j.1365-2125.2007.02974.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic analysis of carboxyhaemoglobin concentrations in adult cigarette smokers

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The pharmacokinetics of carboxyhaemoglobin have been reported previously, primarily with regard to poisoning and toxicity.• Most of these reports have involved noncompartmental analysis of data obtained where the actual dose of carbon monoxide was not known. WHAT THIS STUDY ADDS• This study presents a comprehensive population pharmacokinetic model for carboxyhaemoglobin in adult cigarette smokers.• Since carboxyhaemoglobin is a marker of cigarette smoke exposure, model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 44 publications
6
20
0
Order By: Relevance
“…In our series, men smoking >10 cigarettes/day had a 1.4% increase in haemoglobin compared to non-smokers, whereas in women, the increase was on the average 3.5%, which is in accordance with the carboxyhaemoglobin levels of 3-6% reported in smokers [14,17]. "Normalization" of haemoglobin after smoking cessation has likewise been reported in humans [7,8].…”
Section: Smoking and Alcohol Vs Serum Ferritinsupporting
confidence: 77%
“…In our series, men smoking >10 cigarettes/day had a 1.4% increase in haemoglobin compared to non-smokers, whereas in women, the increase was on the average 3.5%, which is in accordance with the carboxyhaemoglobin levels of 3-6% reported in smokers [14,17]. "Normalization" of haemoglobin after smoking cessation has likewise been reported in humans [7,8].…”
Section: Smoking and Alcohol Vs Serum Ferritinsupporting
confidence: 77%
“…The amount of COHb in the blood depends on duration of CO exposure, CO concentration in inspired air, and alveolar ventilation [6]. Similarly, elimination half-life depends on duration of exposure, concentration, alveolar ventilation, and peak level of COHb [5,6,9]. Most available data for COHb half-life are from acute exposures where subjects were administered supplemental oxygen; these data have suggested a relatively short half-life of 74 to 137 minutes [5].…”
Section: Discussionmentioning
confidence: 98%
“…Carbon monoxide is a tasteless and odorless gas that binds to Hb with an affinity more than 200 times that of O 2 ; CO actively displaces O 2 from Hb to form COHb [5,6]. Carbon monoxide inhaled by smoking may cause tissue hypoxia both by this decrease in blood O 2 content and also by a COinduced shift in the O 2 -Hb dissociation curve to the left, which impedes release of O 2 to tissues [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, kinetics for CO elimination in smokers has been investigated. The result showed two-compartmental kinetics with half-life of 1.6 h for the first phase and 30.9 h for the second phase (Cronenberger et al, 2007). One study suggests that blood donors avoid cigarettes for 24 h before blood donation.…”
Section: Paper IVmentioning
confidence: 99%
“…Some have claimed that CO follows first orders kinetics with one compartmental elimination (Kreck et al, 2001;Sasaki, 1975;Weaver et al, 2000), while others speculate that it has second or multi-compartmental elimination (Shimazu et al, 2000;Wagner et al, 1975); (Wazawa et al, 1996). In a population pharmacokinetic study investigating the elimination time for CO in smokers, the results showed twocompartmental kinetics with a half-life of 1.6 h for the first phase and 30.9 h for the second phase (Cronenberger, Mould, Roethig, & Sarkar, 2007). In that study 190 smokers participated and a mathematic model to predict COHb fractions in adult smokers was developed.…”
Section: Kinetics Of Carbon Monoxidementioning
confidence: 99%